A Gas Seepage Modeling Study for Mitigating Gas Accumulation Risk in Upper Protective Coal Seam Mining Process. (23rd December 2018) - Zhang, Cun; Zhang, Lei; Li, Mingxue; Wang, Chen
Abstract : Protective coal seam mining (PCSM) is one of the most significant mitigation measures of regional outburst in the process of deep coal seam mining, which has high outburst risk in China. During the PCSM process, the phenomenon of methane concentration exceeding the limit usually occurs in the working face. It is vital to understand factors affecting gas emission from the protective seam working face (PSWF) and to obtain an equation for determining the quantity of gas emission. A gas seepage model (GSM) was developed to simulate the gas emission during the process of upper PCSM. In this study, an equation was formulated to determine the quantity of gas desorbed from the protected seam into PSWF. These equations have been developed by using Fick's second law of diffusion and Darcy's flow law. The relationship between permeability and stress was described in an elastic-plastic state, and the mechanics of surrounding rock were investigated. It can be concluded from GSM that the initial gas pressure of protected seam, the characteristics of interlayer rocks, and the ventilation pressure of PSWF were the main factors that influenced the desorption of gas emission from the protected seam into PSWF. The developed GSM was tested for calculating gas emission quantity from the PCSM process by utilizing the actual geological condition data of a coal mine, which is located in Hancheng, China. The results have shown great agreement with obtained field measurements, which is done by combining the fitting curve of ventilation air methane quantity for PSWF with an interlayer spacing. A loss coefficient ( δ ) of 1.012 × 10 −3 was obtained in this study.